Evaluation of short-term clinical outcomes of subacromial impingement patients with performed arthroscopic subacromial decompression - Sarikaya, Baran (Annals of Medical Research, 2021)
Aim: In this study, it was aimed to evaluate short-term clinical outcomes of arthroscopic subacromial decompression procedure which was performed on patients who had subacromial impingement syndrome and did not respond to conservative treatment.Materials Methods: Patients who did not have any shoulder disorder including rotator cuff rupture or capsulolabral pathologies, but subacromial impingement syndrome were evaluated retrospectively. The patients were evaluated clinically according to the Constant-Murley scoring system and visual analog scale (VAS). Active and passive ranges of motion of the joint of the patients were evaluated both preoperatively and at the final follow-up.Results: A total of 64 patients were evaluated. Of the patients; 22 were male and 42 were female and 54 (29-77) was determined to be the mean age. Mean follow-up duration was 17.4 months (7-25 months). The preoperative mean Constant-Murley score was 52 (36-79), whereas it was determined to be a mean of 79 (48-98) at the final follow-up. VAS was determined to be 7.2 (5-9) preoperatively, whereas it was determined to be 2 (0-5) at the final follow-up. Statistically significant differences were determined for both scoring systems at the final follow-up compared with the preoperative period (p0.001).Conclusion: Satisfactory short-term outcomes may be acquired after arthroscopic subacromial decompression procedure which is performed due to subacromial impingement syndrome for patients who do not respond to conservative treatment.Keywords: Subacromial; Impingement; Arthroscopic.